2016
DOI: 10.1159/000452673
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient Knowledge of Longitudinal Melanonychia: A Survey Study of Patients in Outpatient Clinics

Abstract: Importance: Subungual melanoma (SM) is a rare subtype of cutaneous melanoma but carries a worse prognosis than similarly staged cutaneous melanomas. Assessing patient knowledge of melanonychia is integral to early diagnosis of SM. Objectives: The aim of this paper is to determine patient knowledge of longitudinal melanonychia (LM) and warning signs for SM, frequency of nail self-examinations, and satisfaction of patients with their physician's nail examinations. Design, Setting, and Participants: We conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…However, the high morbidity and mortality associated with nail melanoma highlights the need for recognition of clinical and dermoscopic features that can clue clinicians in to the need for a nail unit biopsy. Moreover, most patients do not recognize nail abnormalities associated with a subungual melanoma ( Halteh et al, 2017 ) and may not present for changes regarding the nail unit. Features of pigmented nail lesions are best appreciated with contact dermoscopy, under polarized light, with the use of gel immersion, such as ultrasound gel ( Braun et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the high morbidity and mortality associated with nail melanoma highlights the need for recognition of clinical and dermoscopic features that can clue clinicians in to the need for a nail unit biopsy. Moreover, most patients do not recognize nail abnormalities associated with a subungual melanoma ( Halteh et al, 2017 ) and may not present for changes regarding the nail unit. Features of pigmented nail lesions are best appreciated with contact dermoscopy, under polarized light, with the use of gel immersion, such as ultrasound gel ( Braun et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…Aggressive tumor behavior, 7,19,20 poor biopsy technique or failure to biopsy in the earliest disease stages, 7,11,21‐29 likely contribute to the poor prognosis associated with SUM. Physicians may lack confidence in performing biopsies in the subungual region due to complex anatomy, lack of formal nail biopsy training and poor familiarity with clinical and dermoscopic of SUM due to the rarity of the disease 3,23,29‐34 . Because risks factors for SUM are unknown, early detection is the currently only way to potentially improve survival and functionality in these patients 24,35,36 …”
Section: Discussionmentioning
confidence: 99%
“…likely contribute to the poor prognosis associated with SUM. Physicians may lack confidence in performing biopsies in the subungual region due to complex anatomy, lack of formal nail biopsy training and poor familiarity with clinical and dermoscopic of SUM due to the rarity of the disease 3,23,[29][30][31][32][33][34]. …”
mentioning
confidence: 99%
“…A previous survey-based study found a paucity of patient knowledge on longitudinal melanonychia and the warning signs for subungual melanomas. 3 Only 31% of patients assessed their nails for color changes, and only 13% of patients responded that their doctors asked about nail changes. Another study found that only 8% of physicians asked their patients to remove nail polish at every visit, yet 44% of physicians responded that they encounter melanonychia at least once a month and 23% once a week.…”
mentioning
confidence: 99%